Korelasi Aminotransferase Platelet Ratio Index (APRI) Dengan Kadar Bilirubin Serum Pada Penderita Sirosis Hepatis Akibat Infeksi Virus Hepatitis C Di RSUD Dr. H. Abdul Moeloek Lampung - Vira Katya Aurelia; Intanri Kurniati (CV. Jasa Sukses Abadi, 2022)
Hepatitis C is an Inflammation in Liver because of Hepatitis C Virus (HCV). When HCV turning into the bloodstream and enter the liver, HCV will attached to liver cells and starting proliferate. Liver cells becomes broken and causing fibrosis. When in the fibrosis phase, Trombopoietin will in the lower phase and thrombocytopenia will happen. An enzyme that most associated with the destruction of the liver cells is AST and ALT. APRI is apredictor of the cirrhosis progressivity with 81% sensitivity to assess the severity of cirrhosis that APRI is the patients AST value and the platelet. In liver cirrhosis will turns into hyperbillirubine. Intrahepatic phase involves inflammation or abnormalities in the liver that interfere with the removal of bilirubin. This study aims to determine the correlation between APRI and serum bilirubin levels and the mean correlation between AST, ALT, platelets and serum bilirubin levels in patients with hepatic cirrhosis due to hepatitis C virus infection at RSUD Dr . H. Abdul Moeloek Lampung. This study used a consecutive sampling research design and was conducted in June-July 2020. The study sample was 51 subjects. The data used in this study are secondary data, namely medical records. The case group consisted of 27 male patients and 24 female patients. Data were analyzed using Pearson test. : The results of bivariate analysis between APRI and serum bilirubin levels showed a p value of 0.000 which indicates a positive and very strong correlation between APRI and serum bilirubin levels, positive and strong correlation between AST and ALT with serum bilirubin levels, and negative and sufficient correlation between platelets and Serum Bilirubin levels in patients with hepatic cirrhosis due to hepatitis C virus infection at Dr. H. Abdul Moeloek Lampung